How the Aid Industry works the politics and practice of international development - Haan, Arjan de 1963- (Kumarian Press, 2023)
International development assistance-what Arjan de Haan calls the aid industry-continues to be critical for overcoming the world's development challenges, perhaps more so than ever given the global realities of climate change and the Covid pandemic. But how does this industry actually work? What practices does it follow, and to what effect? De Haan addresses these questions, providing a concise introduction to the business of development. This new edition reflects fifteen years of increasing complexity in the aid industry: heightened polarized debates about appropriate approaches; the involvement of new donors, such as China; adoption of the Sustainable Development Goals; the blending of public- and private-sector investment; tensions among charitable, political, and commercial considerations. The list goes on. De Haan incorporates these factors in a succinct overview that is an ideal introduction for students encountering the subject of development for the first time, as well as a handy overview for development practitioners.